Challenges Faced by Jordan’s Search and Rescue Team in the 2023 Turkey Earthquake; A Qualitative Study from Readiness to Response - Alwidyan, Mahmoud T.; Al Ruwaithi , Abdulhadi A.; Alrawashdeh, Ahmad; Bashier, Haitham; Al-smeiat, Marwan; Ikhwayleh, Zuhair A.; Alruwailli, Abdullah S.; Khader, Yousef S. (Archives of Academic Emergency Medicine, 2025)
Introduction: Many international search and rescue teams were deployed to the devastating earthquake of Southeastern Turkey and Northern Syria on February 6th, 2023, including the Jordan International Search and Rescue Team (JSAR). This study aims to explore the challenges faced by the JSAR team members during their deployment. Methods: We employed a qualitative face-to-face semi-structured interview approach. Eighteen respondents were interviewed using an interview guide. Interviews took between 25 and 60 minutes (mean 45 minutes). Data were transcribed verbatim and an inductive thematic approach was used to analyze data and develop codes, categories, and themes. Results: The challenges were categorized into three main themes; logistical, coordination, and environmental. Logistical challenges included delays in deployment due to government and flight arrangements, difficulties in transporting excess equipment, and a lack of fuel upon arrival that led to delays in setting up camp and heating. Coordination challenges involved disruption in operation schedule and difficulties working with local volunteer responders. Environmental challenges encompassed extreme cold temperatures, which affected personnel comfort and performance, and recurrent aftershocks, which complicated rescue operations and posed safety risks. Conclusion: The JSAR experience highlights that technical readiness alone is insufficient for effective disaster response. Findings from this study underscore significant gaps in logistics, coordination, and environmental adaptation. These gaps can be addressed through improved pre-deployment coordination, context-specific resource planning, and better collaboration mechanisms between host countries and international teams, which would be crucial for enhancing the effectiveness of international search and rescue operations. Host governments, International Search and Rescue Advisory Group (INSARAG) stakeholders, and emergency management bodies can build on these lessons to better integrate specialized teams, reduce procedural delays, and enhance global disaster response systems.